OTIN E.S. DICTIONARY OF THE RUSSIAN LANGUAGE (X-XVIII CENTURIES). Donetsk: Southeast, 2014. 436 pp (Proceedings of Southern Federal University. Philology, 2015)
E.V. Serdyukova The paper provides an overview of the new single-volume historical "Dictionary of the Russian language (X-XVIII centuries)" by E.S. Otin published in Donetsk in 2014 (recommended for publishing by the Academic Council of Donetsk National University). The author points out the advantages of the dictionary, as well as a few shortcomings in the presentation of the material in the dictionary. Keywords: historical dictionary, E.S. Otin, dictionary of the Russian language.